Design principles for electrically driven Luttinger liquid-fed plasmonic nanoantennas - Jeon Eun Su; Ko YoonYeong; Yoo SeokJae (Nanophotonics)
Electrons injected into one-dimensional (1D) metals are efficiently converted into infrared plasmons because the unique property of the Luttinger liquid, a strongly correlated electronic matter in one-dimensional (1D) metals, prohibits excitations of other quasiparticles. Using the Luttinger liquid behavior, the electrically driven 1D metals can be used as a feed for optical nanoantennas. Nanoantennas can couple the 1D Luttinger liquid plasmons in the feed to the radiating photons in free space. In this work, we suggest design principles for the 1D metallic Luttinger liquid feed and the nanoantennas to obtain high injection and radiation efficiencies, respectively. We expect that our work can promote experimental efforts to realize electrically driven Luttinger liquid-fed nanoantennas and efficient infrared light sources.